Uncertainty and my healthy narrative. Issue 3 (2nd July 2020) - Boait, Ed
ABSTRACT: Learning to live well with Schizophrenia has taken a long time and a lot of therapy. Having had a large number of psychotic episodes means that the narrative I hold about my life has gone through many changes. Here is the story of the lead up to my first experience of psychosis and it changed everything I thought about myself and my life. The idea is that I have reflected on the different stories, with the aim that my current narrative works for me, that it is a healthy narrative. There is a big difference between my manic narrative and my depressive narrative, and recently I have been able to find some middle ground, mostly because I now am able to hold a lot of uncertainty. My healthy narrative has many paradigms that allow me to find meaning without needing to be certain of the facts. That was the great problem with my grandiosity, it generated a huge number of fake facts, things that had just not happened and yet I totally believed they had. Now, with greater flexibility of what has happened in my life, I am able to live happily and use my knowledge to help other people.